Another Side of North Korea: Business for Profit - Choe, Sang T.; Mahoney, Timothy B. (Journal of Marketing Development and Competitiveness, 2018)
As one of the remaining five communist countries on earth, North Korea became infamous in recent years with its nuclear issues with the outside world and political instability inside the country. This paper, looks at North Korea from a different angle to identify its strengths and potentials in the future to become a productive global citizen by identifying five key factors; (1) untapped underground resources, (2) economic geography favorable for effective supply chain via land routes, (3) affordable labor force with discipline and education, (4) people’s desire to achieve economic wellbeing, and (5) latent needs of variety of consumer goods.